Povertà valoriale, povertà educativa. Il prisma pandemico: L’approdo pandemico - Corsi, Michele (Rivista Italiana di Educazione Familiare, 2022)
The paper analyzes a limited period: namely, from March 2020 to April 2021, with a particular eye on Easter 2021, in Italy. To get to the present day. In which the pandemic acts as a unit of investigation, or a magnifying glass, to support the link between axiological poverty and educational poverty, as it is in the intentions, or in the interpretation, of the author. In a pedagogical control room, or a frame of reference. Dwelling, specially, on the younger generations, as well as on schools and families. Last but not least, on parents or adults in general, in the current Italian social and economic context. Going to investigate the two personal and relational behaviors or attitudes that seem to prevail in most of the national population from adolescence onwards: distrust and suspicion. Which are the fallout from the great forgotten of the most recent three or four decades: education. In conclusion, the author hopes for a post-pandemic reconstruction including educational, relational, social and politic values.